Інноваційне управління підприємством в сучасних умовах - Передрій, Андреа Елізабет Юріївна (НТУ "ХПІ", 2017)
У статті розглянуто методичні підходи до визначення сучасних методів інноваційного управління підприємствами. Проведено детальний аналіз розвитку менеджменту підприємств. Сформовано рекомендації по забезпеченню нового рівня інноваційного управляння, яке дозволить створювати довгострокові переваги і забезпечити гідне місце на ринку, бути конкурентоспроможними. На зміну старим принципам менеджменту 1.0 прийшов час застосовувати новий менеджмент 2.0., який пов'язаний с цінністно-орієнтованим управлінням (психологією, та духовністю людини, з творчістю тощо).

The article considers methodological approaches to the definition of modern methods of innovative management of enterprises. A detailed analysis of the development of enterprise management was carried out. The recommendations on the provision of a new level of innovative management have been formulated, which will create long-term advantages and provide a worthy place in the market, be competitive. Society and economy are faced with changes that are characterized by greater complexity, speed, diversity, scale, multidimensionality, randomness, uncertainty and unpredictability, new risks and opportunities In place of the old principles of management 1.0, it's time to apply the new management 2.0, which is connected with value-oriented management (psychology, human spirituality, creativity, etc.).
Innovative management of the enterprise in modern conditions
Keywords: інновації; менеджмент; виробництво; ефективність; innovation; management; production; efficiency